Investigating Thermal and Surface Properties of Low‐Density Polyethylene/Nanoperlite Nanocomposites for Packaging Applications. Issue 7 (12th October 2018) - Heidari, Behzad Shiroud; Davachi, Seyed Mohammad; Sahraeian, Razi; Esfandeh, Masoud; Rashedi, Hamid; Seyfi, Javad
Abstract : Nanocomposites films based on low‐density polyethylene (LDPE) and different compositions of treated and untreated nanoperlite were prepared via melt mixing of the ingredients on a corotating twin‐screw extruder and then film blowing the nanocomposites. The physical dispersion of the nanocomposites is confirmed using Fourier transform infrared‐attenuated total reflectance (FTIR‐ATR) method. According to the thermal studies, the nanocomposites with untreated nanoperlite showing higher melting temperature and crystallinity, while their thermal stability is lower than nanocomposites with treated nanoperlite. The thermal and FTIR‐ATR studies also revealed the ethylene absorption of the nanocomposites. According to the surface energy results, the treatment of the nanoparticles completely changes the surface behavior and hydrophobicity of the films. Finally, peel color index and field study observations showed that increase in nanoperlite will increase the shelf life of the fruits; however, the nanocomposite with 6% untreated nanoperlite is the best choice for the packaging applications. POLYM. COMPOS., 40:2929–2937, 2019. © 2018 Society of Plastics Engineers